"Two Courts" for One Constitution: Fragmentation of Constitutional Review in the Law of the Kosovo Specialist Chambers in The Hague. Issue 2 (17th February 2023) - Hasani, Enver; Korenica, Fisnik
Abstract: The Kosovo Specialist Chambers embody a remarkable project involving elements of the domestic law of the Republic of Kosovo, the EU's external relations law, and international criminal law. The Chambers' hybrid nature is not only unique, but also atypical in regards to its influence in Kosovo's constitutional order. The Specialist Constitutional Chamber is one of the instances of the Kosovo Specialist Chambers sitting in the Hague. The Specialist Constitutional Chamber resembles Kosovo's Constitutional Court on a specific, though exclusive, area of law—the law surrounding the court in general. The two courts not only exercise the same generic function—on the basis of exclusive material criteria—but also possibly parallel and compete with each other. The relationship between the "two courts" is at best explained with the term "fragmentation of constitutional jurisdiction." While the two courts are forced to endure under the same normative roof—the Constitution—they inherently exercise often conflicting functions and protect irreconcilable ideological perspectives. The article examines the interaction between the two courts primarily in a normative and jurisdictional perspective. It also presents recent tendencies of both courts to divert in divergent pathways. The article concludes that while the two courts present an unobserved case in comparative constitutional law, they also reveal an interesting and unconventional constitutional controversy appearing in the context of a sovereign country's relationship with international law obligations.